2005
DOI: 10.1002/jsfa.2208
|View full text |Cite
|
Sign up to set email alerts
|

Resistant starch production from mango starch using a single‐screw extruder

Abstract: Resistant starches were prepared from mango starch by extrusion. An experimental design with independent variables temperature, screw speed and moisture content produced 20 samples that were studied to determine the effect of these variables on resistant starch (RS) content, water absorption index (WAI) and water solubility index (WSI). RS content was affected by moisture content and temperature. Screw speed and temperature also influenced RS content, the highest level (97 g kg −1 ) being obtained at low screw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 29 publications
(16 reference statements)
4
36
0
Order By: Relevance
“…The WHC and OHC values in our study were similar to the values of mango peels reported by Larrauri et al (1996b). High WHC may be due to the presence of high soluble fibre substances (Agustiniano-Osornio et al, 2005). No significant difference (P > 0.05) was found between the FRP and commercial cellulose ( Table 2).…”
Section: Proximate Compositionsupporting
confidence: 87%
“…The WHC and OHC values in our study were similar to the values of mango peels reported by Larrauri et al (1996b). High WHC may be due to the presence of high soluble fibre substances (Agustiniano-Osornio et al, 2005). No significant difference (P > 0.05) was found between the FRP and commercial cellulose ( Table 2).…”
Section: Proximate Compositionsupporting
confidence: 87%
“…Pulp of unripe mango is characterized by containing starch (BelloPe´rez, Ottenhof, Agama-Acevedo, & Farhat, 2005;Kaur, Singh, Singh-Sandhu, & Singh-Guraya, 2004). TS content in the fibre concentrate was of 29.8 g/100 g dry sample (Table 2); such a high starch level that could contribute to the formation of resistant starch (RS) during processing of MDF-based products, as it has been shown in mango starch extrudates (Agustiniano-Osornio et al, 2005). Total dietary fibre (TDF) content in MDF was 28.1 g/100 g dry sample (Table 2), which is close to levels measured in antioxidant DF preparations from guava (48-49 g/100 g dry sample) (Jime´nez-Escrig, Jime´nez-Escrig, Rinco´n, Pulido, & Saura-Calixto, 2001), although notably lower than TDF contents reported in grape skins (54.1-64.6 g/100 g dry sample) (Bravo & SauraCalixto, 1998;Saura-Calixto, 1998), citrus peel (57 g/100 g dry sample) (Chau & Huang, 2003), in fibre from two Mexican lime peels (66.7 and 70.4 g/100 g dry sample) (Ubando et al, 2005) and in mango peel fibre (65-71 g/ 100 g dry sample) (Larrauri et al, 1996).…”
Section: Chemical Compositionmentioning
confidence: 94%
“…This pattern resulted because the extrusion treatment led to starch depolymerization and linear chains showing a higher tendency to form structures presenting low enzymatic digestibility [65,66]. Because the gelatinization temperature of this starch was 70°C, its amylose content was important in this pattern [4].…”
Section: Extrusionmentioning
confidence: 97%
“…Another method for RS production involves starch gelatinization, enzymatic debranching of the gelatinized polymer, deactivation of the debranching enzyme, and isolation of the resultant product either by drying, extrusion, or crystallization [27]. Extrusion has been claimed as a unit operation for RS production; however, the RS levels obtained with this procedure are lower than those prepared using autoclaving [4,107].…”
Section: Resistant Starch Productionmentioning
confidence: 99%
See 1 more Smart Citation